Vogt-Koyanagi-Harada disease: a retrospective and multicentric study of 41 patients - K. Diallo; S. Revuz; G. Clavel-Refregiers; T. Sené; C. Titah; M. Gerfaud-Valentin; P. Seve; R. Jaussaud (BMC Ophthalmology, 2020)
Abstract Background East and South East Asian subjects as well as Amerindians and Hispanic subjects are predominantly affected by Vogt-Koyanagi-Harada disease. In Europe, only few studies have described the clinical features and treatment of this disease, especially in France. Methods This retrospective case series was based on data collected from patients with a VKH disease diagnosed from January 2000 to March 2017, provided by three French Tertiary Centers. Results Forty-one patients (16 men and 25 women) were diagnosed: average age at diagnosis was 38.7 years. Patients were mainly from Maghreb (58%), but ethnic origins were multiple. Pleiocytosis was observed in 19 cases (63%) and 17 out of 41 patients showed audio vestibular signs (41%), and 11 showed skin signs (27%). Thirty-four were treated with corticosteroids (83%), 11 with an immunosuppressant treatment (27%) and 5 with biological therapy drugs (13%). Relapse was observed in 41% patients, even though final average visual acuity had improved. We did not find any significant clinical difference in the population from Maghreb compared to other populations, but for age and sex trends, since there was a majority of younger women. Conclusion We report here the second largest French cohort reported to date to our knowledge. The multiethnicity in our study suggests that VKH disease should be evoked whatever patients’ ethnicity.